The Effect of Interactive User Journey and Retargeting Strategy on Final Conversion and Shopping Satisfaction of Generation Z in Indonesian Mobile E-Commerce - Novitasari, Salwa Aulia; Baso, Andi Sabirin; Munayang, Olivia H. (West Science Social and Humanities Studies, 2025)
This study aims to analyze the influence of the Interactive User Journey and Retargeting Strategy on Final Conversion and Shopping Satisfaction among Generation Z mobile commerce users in Indonesia. Using a quantitative approach with 120 valid responses and Structural Equation Modeling–Partial Least Squares (SEM-PLS) 3, the study investigates direct and indirect relationships between variables. The results show that both interactive user journey and retargeting strategy significantly and positively influence final conversion and shopping satisfaction. Additionally, final conversion acts as a partial mediator, strengthening the impact of both independent variables on shopping satisfaction. These findings underscore the critical importance of user-centric design and personalized marketing in enhancing conversion rates and satisfaction in mobile commerce platforms, particularly for the Gen Z demographic. The study provides both theoretical contributions to digital consumer behavior literature and practical insights for mobile commerce managers and digital marketers.